The Neural Baroreflex Pathway in Subjects With Metabolic Syndrome: A Sub-Study of the Paris Prospective Study III. Issue 2 (January 2016) - Zanoli, Luca; Empana, Jean-Philippe; Estrugo, Nicolas; Escriou, Guillaume; Ketthab, Hakim; Pruny, Jean-Francois; Castellino, Pietro; Laude, Dominique; Thomas, Frederique; Pannier, Bruno; Jouven, Xavier; Boutouyrie, Pierre; et al.
Abstract : Abstract: The mechanisms that link metabolic syndrome (MetS) to increased cardiovascular risk are incompletely understood. We examined whether MetS is associated with the neural baroreflex pathway (NBP) and whether any such associations are independent of blood pressure values. This study involved the cross-sectional analysis of data on 2835 subjects aged 50 to 75 years from the Paris Prospective Study 3. The prevalence of MetS was defined according to the American Heart Association/National Heart Blood and Lung Institute definition. NBP values were calculated from the fluctuation of the common carotid distension rate and heart rate using fast Fourier transformation and cross-spectral analysis. The prevalence of MetS was 20.1% in men and 10.4% in women. Compared with controls, subjects with MetS (≥3 components), and those at risk for MetS (1–2 components) had lower NBP (−5.3% and −2.3%, respectively) and higher carotid stiffness (+13.5% and +6.8%, respectively). The negative association between MetS components and NBP was confirmed, even after adjustment for age, sex, and carotid stiffness. After stratification for blood pressure (BP) levels, NBP was reduced only in MetS subjects and those at risk with high BP. The NBP was positively associated with carotid stiffness in controls and subjects at risk for MetS. This association was lost in subjects with MetS, regardless of BP levels. Subjects with MetS had reduced NBP values. The role of BP is fundamental in the reduction of NBP. The mechanisms that link carotid stiffness and NBP are inactive in subjects with MetS, independent of BP levels.